2014
DOI: 10.1590/0103-6440201302260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Titanium Surfaces on the Developmental Profile of Monocytes/Macrophages

Abstract: Due to the critical role of monocytes/macrophages (Mφ) in bone healing, this study evaluated the effects of bio-anodized, acid-etched, and machined titanium surfaces (Ti) on Mφ behavior. Cells were separated from whole human blood from 10 patients, plated on Ti or polystyrene (control) surfaces, and cultured for 72 h. At 24, 48 and 72 h, cell viability, levels of IL1β, IL10, TNFα, TGFβ1 inflammatory mediators, and nitric oxide (NO) release were analyzed by mitochondrial colorimetric assay (MTT assay) and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Bio-anodized, acid-etched, and machined titanium surfaces (Ti) do not influence macrophage viability and do not induce a macrophage cytokine release (IL1-β, TNF-α and TGF-β1) significantly different compared to the Ti surfaces. Furthermore, the Ti surface characteristics do not induce a typical Th1 or Th2 cytokine profile, suggesting that titanium surfaces are inert to monocytes/macrophages and do not change the characteristics of the cell response [249].…”
Section: Tunable Properties Of Biomaterialsmentioning
confidence: 99%
“…Bio-anodized, acid-etched, and machined titanium surfaces (Ti) do not influence macrophage viability and do not induce a macrophage cytokine release (IL1-β, TNF-α and TGF-β1) significantly different compared to the Ti surfaces. Furthermore, the Ti surface characteristics do not induce a typical Th1 or Th2 cytokine profile, suggesting that titanium surfaces are inert to monocytes/macrophages and do not change the characteristics of the cell response [249].…”
Section: Tunable Properties Of Biomaterialsmentioning
confidence: 99%
“…Other studies have also suggested that compared to smooth surfaces, surfaces that contain microscale features appear to enhance the adhesion of macrophages and their secretion of inammatory cytokines, including IL-1b, IL-6, and nitric oxide. [53][54][55][56] Besides, studies have conrmed that compared with a microscale morphology, a nanoscale morphology inhibits the secretion of inammatory cytokines and the synthesis of NO in macrophages. 13,57 Therefore, we speculated that the nanoscale wrinkles and decreased roughness of the surface formed by GO were involved in the higher expression of M2 phenotype-related markers in macrophages cultured on this surface than in macrophages cultured on the SLA surface.…”
Section: Macrophages Polarizationmentioning
confidence: 99%
“…However, recent evidence suggests that material geometry, or size and shape, may in fact dominate the overall response. Biomaterial surface microtopography has also been explored as physical cue to control the host response, and offers the advantage of long-term stability and cost-effective fabrication methods. Studies have generally suggested that surfaces that contain microscale features appeared to enhance the adhesion of macrophages and their secretion of inflammatory cytokines including IL-1β, IL-6, and nitric oxide when compared to macrophages on smooth surfaces. More recently, it has been suggested that the degree of roughness is important, since TiO 2 surfaces that were moderately roughened induced polarization toward a pro-healing phenotype, whereas greater roughness led to inflammatory activation . Precisely engineered microfabricated substrates have further helped to elucidate the effects of topography on macrophage behavior and the host response.…”
Section: Introductionmentioning
confidence: 99%